The Cultural Roots of Effective Institutions - Philippe d’Iribarne; Henry, Alain (World Bank, Washington, DC, 2017)
In many countries, the resistances that obstruct the setting-up of development-enhancing forms of governance are problematic. In many cases, these resistances are linked to firmly anchored beliefs that have to do with to the proper ways of acting in society. For many years, much was expected from a cultural modernization that was to bring about a radical change in attitudes and beliefs. But in many places, the positive behavioral changes observed seem to relate more to making the most of the potentialities inherent to the cultures concerned. This paper begins in analyzing how the appeal of such positive potentialities has materialized in the countries that served as the laboratories of modernity. The second part is grounded in observations made in emerging countries, identifying modern institutional systems that best take advantage of the cultural context. This paper shown that successful organizations make good creative use of the local cultural context.